Penerapan Terapi Musik Religi terhadap Nyeri pada Pasien Fraktur di Bangsal Flamboyan 5 RSUD Dr. Moewardi Surakarta - Opie Yunia Widiati; Eska Dwi Prajayanti; Isti Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
Fracture is a condition in which the bone structure is severed or damaged due to external pressure on the bone. Fractures can be caused by direct impact, sudden twisting movements, or even by extreme muscle contractions. The WHO states that the prevalence rate of fractures increased from 2020 by approximately 13 million (2.7%). The Ministry of Health in 2023 stated that in Indonesia around 8 million people had fractures. To determine the results of the application of religious music therapy on pain in fracture patients in Flamboyant Ward 5 of Dr Moewardi Surakarta Hospital. The application uses a case study method with a research sample of 2 respondents, the research instrument uses NRS. The intervention group reduced pain from a scale of 6 to 4, and in the control group reduced pain from a scale of 5 to 4. From this study it can be concluded that religious music therapy is more effective to reduce pain.